Timeline of the Concept of Child Regulations Out of Wedlock (Study of Family Law Rules in Indonesia) - Luthfi, Muhammad; Kurniawan, Kukuh Dwi; Fajrin, Yaris Adhial; Wardoyo, Yohana Puspitasari; Nuryasinta, Radhityas Kharisma (KnE Social Sciences, 2024)
Rules regarding children out of wedlock in Indonesia are divided into three laws starting from the Marriage Law, the Presidential Instruction on KHI, and the Civil Code. Following the Constitutional Court Decision No.46/PUU-VII/2010 the rules regarding children out of wedlock in the Marriage Law have also undergone re-reading. Each legal regulation for children out of wedlock has different legal consequences, so it is interesting to study about the concept of children out in the timeline of civil law regulations in Indonesia. This paper aimsis to find out the concept of children out of wedlock in the timeline of legal regulations in Indonesia. This research uses normative legal research with a statutory approach. The results of this study stated that the regulation of children out of wedlock was accommodated after the recognition of the Civil Code in the Indonesian legal system. On January 2, 1974 the provision of children out of wedlock was regulated in Article 43 paragraph (1) of the Marriage Law, after the promulgation of the Presidential Instruction on KHI the provision of children out of wedlock was regulated in Article 100 of the Presidential Instruction on KHI where children out of wedlock only had civil rights with the mother and her mother’s family. And, Constitutional Court Decision No.46/PUU-VII/2010 makes children out of wedlock have civil rights with their mother and father as long as it can be proven by technology and science. Keywords: timeline, concept, child regulations out of wedlock, family law, Indonesia